2001
DOI: 10.1046/j.1365-8711.2001.04875.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of active galactic nuclei broad-line region clouds: low- and high-ionization lines

Abstract: The formation of quasar broad‐line region (BLR) clouds via thermal instability in the presence of Alfvén heating has been discussed by Gonçalves, Jatenco‐Pereira & Opher. In particular, these studies showed the relevance of Alfvén heating in establishing the stability of BLR clouds in the intercloud medium. The present paper shows the results of time‐dependent calculations (we use a time‐dependent hydrodynamic code) following the evolution of BLR clouds, since their formation from the 107‐K intercloud medium. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However this is extremely challenging, firstly because of the relatively low statistical significance of any additional excess, secondly because we modeled the BLR using an average source flux that possibly introduces more scatter in the predicted values of the X-ray lines luminosity. Being able to study a part of the BLR which only emits in the X-ray band would be indeed very important in understanding the stratification of the BLR and its velocity field (e.g., Baldwin 1997;Gonçalves et al 2001). Following further the BLR interpretation, we find that the luminosity-weighted radii (Sect.…”
Section: Emission From the Broad Line Regionmentioning
confidence: 58%
“…However this is extremely challenging, firstly because of the relatively low statistical significance of any additional excess, secondly because we modeled the BLR using an average source flux that possibly introduces more scatter in the predicted values of the X-ray lines luminosity. Being able to study a part of the BLR which only emits in the X-ray band would be indeed very important in understanding the stratification of the BLR and its velocity field (e.g., Baldwin 1997;Gonçalves et al 2001). Following further the BLR interpretation, we find that the luminosity-weighted radii (Sect.…”
Section: Emission From the Broad Line Regionmentioning
confidence: 58%
“…Others have shown that dissipative MHD heating has a similar stabilizing influence on the BLR gas itself (Goncalves, Jantenco-Pereira, & Opher 1996). Finally, the low-density gas that forms the putative intercloud medium of the BLR may provide a significant contribution to line emission if the low-density gas is MHD turbulent and dissipative (Goncalves, Friaca, & Jantenco-Pereira 2001).…”
Section: Nonthermal Motions In Agn Emission-line Cloudsmentioning
confidence: 98%